2010
DOI: 10.1253/circj.cj-09-0800
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiac Allograft Vasculopathy by Multidetector Computed Tomography and Whole-Heart Magnetic Resonance Coronary Angiography

Abstract: Background: Cardiac allograft vasculopathy (CAV) is a major complication that limits the long-term survival of recipients of heart transplants. In the present study the feasibility of 2 noninvasive approaches for detecting CAV (multidetector computed tomography (MDCT) and whole-heart magnetic resonance coronary angiography (MRCA)) was compared with conventional coronary angiography (CCAG). Methods and Results:Of 22 heart transplant recipients who underwent CCAG screening, 13 had only MDCT, 16 had only MRCA, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Recent reports underline the potential of MDCT to replace conventional coronary angiography for the diagnosis and follow-up of cardiac allograft vasculopathy in heart transplant recipients [5][6][7][8]10]. However, emerging data on exposure to ionising radiation from imaging procedures [27][28][29] and particularly the relatively high radiation dose related to cardiac CT [11,12,31], has raised concern among the medical community about keeping the radiation dose at minimum levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports underline the potential of MDCT to replace conventional coronary angiography for the diagnosis and follow-up of cardiac allograft vasculopathy in heart transplant recipients [5][6][7][8]10]. However, emerging data on exposure to ionising radiation from imaging procedures [27][28][29] and particularly the relatively high radiation dose related to cardiac CT [11,12,31], has raised concern among the medical community about keeping the radiation dose at minimum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Among the different non-invasive imaging techniques routinely employed in the diagnostic work-up of cardiac allograft vasculopathy, i.e. nuclear perfusion tests [3] and stress echocardiography [4], multidetector computed tomography (CT) has emerged as a promising tool to reliably rule out this disease [5][6][7][8]. In particular, dual-source CT (DSCT) has been shown to provide diagnostic image quality in heart transplant recipients [9] while allowing significant coronary allograft vasculopathy to be reliably excluded [10].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed the feasibility of whole-heart MR coronary angiography for detecting CAV. Previous study using CCA as a reference demonstrated limited sensitivity (60%) of this technique, much lower than that by CT coronary angiography using novel multi-detector CT scanners, presumably because of insufficient spatial and temporal resolution [38]. The latter three techniques are more complex and require longer time than PFR measurement for examination, image post-processing, and data analysis.…”
Section: Noninvasive Cav Screeningmentioning
confidence: 97%
“…91 The major drawbacks with the routine use of MDCT after HTx include the high heart rate of patients which might compromise imaging quality, contrast-induced nephropathy, and radiation. 94,95 Compared with IVUS, the sensitivity, specificity, positive and negative predictive values for the detection of CAV by dual source CT were 85%, 84%, 76%, and 91%, respectively. Dual source CT permits the investigation of HTx recipients concerning the presence of CAV with good image quality and high diagnostic accuracy.…”
Section: Computed Tomographymentioning
confidence: 99%